Four Decades of Frontline Service Employee Research: An Integrative Bibliometric Review. (May 2021) - Subramony, Mahesh; Groth, Markus; Hu, Xinyu 'Judy'; Wu, Yu
We conducted a comprehensive review of empirical research related to frontline service employees over the past four decades (1980-2020). Utilizing a bibliometric mapping approach, we identified 630 relevant articles appearing in service, management, marketing, and applied/occupational health psychology journals. Our analysis identified five distinct research clusters: (a) collective predictors and effects, (b) services encounters, (c) emotional regulation and management, (d) customer orientation, and (e) service stress and strain. In this article, we describe the nature of current research within each of these clusters and identify future directions within and across different clusters for scholarly work. Our review highlights the conceptual and methodological richness within the clusters and calls out for interdisciplinary scholarship to build a diverse, yet unified field of service work research.